2022
DOI: 10.1111/raq.12778
|View full text |Cite
|
Sign up to set email alerts
|

Root‐released organic compounds in aquaponics and their potential effects on system performance

Abstract: Optimizing production in aquaponics requires in‐depth knowledge of the plant, fish and microbial compartments. This opinion paper is focused on root‐released organic compounds and their implication in aquaponics, an area that has received little to no direct research to date. Key scientific literature from two distinct fields of study—phytochemicals in aquaculture science and root exudates in plant science—reveals possible pathways and effects. Root exudates, passively or actively released by plants as a stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…from flathead grey mullet intestinal samples, and their almost absence in the other compartments of the aquaponic unit analysed, we hypothesize that the above-mentioned changes might be attributed to the presence in the water of metabolites exuded by lettuce roots that may modulate the growth of some bacteria in fish guts such as those belonging to the genera Brevinema and Streptococcus spp. as different studies have shown that these compounds have the capacity to modify the soil microbiota and their exudation is promoted by flooding among other factors 21,53 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…from flathead grey mullet intestinal samples, and their almost absence in the other compartments of the aquaponic unit analysed, we hypothesize that the above-mentioned changes might be attributed to the presence in the water of metabolites exuded by lettuce roots that may modulate the growth of some bacteria in fish guts such as those belonging to the genera Brevinema and Streptococcus spp. as different studies have shown that these compounds have the capacity to modify the soil microbiota and their exudation is promoted by flooding among other factors 21,53 .…”
Section: Discussionmentioning
confidence: 99%
“…coupled with a decrease in Lewinella (∆ = -5.3%), Nitrospira (∆ = − 3.4%), Reyranella (∆ = − 2.9%) and Pirellula (∆ = − 2.9%) spp. Those changes in www.nature.com/scientificreports/ microbial composition may be attributed to several factors like the inherent evolution in the nutrient content within the hydroponic unit along the grow out process 11 , the competition for resources among bacteria with similar metabolism 11,15 , and lettuce growth and root exudates that play a key role in microbial development in the root zone 21,22,73 . Furthermore, changes in abiotic water parameters may be also responsible for the abovementioned changes in bacterial abundance; in particular, dissolved oxygen, nitrate and sulphate have a strong influence in the aerobic compartments of aquaponic units 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations